The effect of prenatal self-care based on orem's theory on preterm birth occurrence in women at risk for preterm birth - Seyedeh-Mahboobeh Rezaeean; Zahra Abedian; Robab Latifnejad-Roudsari; Seyed-Reza Mazloum; Zohreh Abbasi (Wolters Kluwer Medknow Publications, 2020)
Background: Preterm birth is increasing as a major cause of perinatal complications and mortality in Iran. The present study aimed to investigate the effect of prenatal self-care based on Orem's theory on preterm birth occurrence in women at risk for preterm birth. Materials and Methods: The present clinical trial was conducted on 176 pregnant women at 24-26 weeks at risk for preterm birth in Mashhad, Iran, from December 2015 to October 2016. A multistage sampling method was used in this study. The intervention group (88 pregnant women) received individual self-care education but the control group (88 pregnant women) received only common prenatal care. Results: There was a statistically significant difference between intervention and control groups in terms of preterm birth occurrence (6.80% vs 20.50%) (χ2 = 6.90, df = 1,p = 0.008). The incidence of preterm birth in the intervention group was approximately three times higher than that in the control group. Conclusions: Given that educational interventions could reduce the incidence of preterm birth, it is suggested that the women at risk for preterm birth are trained for prenatal self-care.